2018
DOI: 10.15406/jpnc.2018.08.00360
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mother’s knowledge on importance and need for Child Car Safety Seat in UAE

Abstract: Objectives: To evaluate maternal awareness and perception on child car safety seat usage in Latifa Women and Children Hospital (LWCH), Dubai, UAE and determine the factors contributing to it. Methods: A cross-sectional analytical survey using self-administered questionnaire was performed in two post-natal wards of Latifa Hospital for Women and Children in Dubai. A total of 201 mothers were included in the study. Descriptive analysis, Chisquare test, and logistic regression analysis were performed to find an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although almost ninety percent of the interviewed participants reported that they appropriately restrained their infants, this percentage decreased dramatically with five-to seven-year-old children, with only circa ten percent of the participants claiming to use an appropriate restraint. A previous study in the UAE by Elhalik et al [23] found that only 45.7 percent of parents claimed that they used CRS when leaving the hospital with their newborn child.…”
Section: Factors That Influence Appropriate Restraint Use For Child O...mentioning
confidence: 98%
See 1 more Smart Citation
“…Although almost ninety percent of the interviewed participants reported that they appropriately restrained their infants, this percentage decreased dramatically with five-to seven-year-old children, with only circa ten percent of the participants claiming to use an appropriate restraint. A previous study in the UAE by Elhalik et al [23] found that only 45.7 percent of parents claimed that they used CRS when leaving the hospital with their newborn child.…”
Section: Factors That Influence Appropriate Restraint Use For Child O...mentioning
confidence: 98%
“…Elhalik, El-Atawi and Mahfouz [23] conducted a survey regarding CRS use at the Latifa Women and Children Hospital in Dubai, which is one of the largest maternity and children's hospitals in the UAE. Over a six-month period in 2017-2018, 201 mothers of newborns from two postnatal wards were recruited.…”
Section: Introductionmentioning
confidence: 99%